D-day code name : overlord - Lee, Lanny; Lutz, Gayle; Rhay, Gary ([S.l.] : Dastar Corporation, 2000)
This DVD documentary tellsthe compelling story of the Normandy Invasion and includes rare color footage from the George Stevens collectin at the Library of Congress
Title from title screen
Executive producer, Norm Andersen ; editor, Gayle Lutz ; camera, Colin Sawyer
DVD Format
Subtitles in Malay, English and Chinese
Keywords: World War, 1939-1945 -- Campaigns -- France -- Normandy